Dualisme Loyalitas Sekretariat Badan Adhoc: Antara Tanggung Jawab Kepada KPU Kabupaten dan Tugas sebagai Aparatur Sipil Negara - Asyadi, Maskup; Warastuti, Reyta (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2022)
The PPK and PPS Sekretariat is an inseparable part of the recruitment system, and it holds an important role as the supporting system in the Elections. The PPK and PPS Sekretariat recruitment is integrated in the 2020 Simultaneous Elections which is contained in the Republic of Indonesia General Elections Commission/KPU Decree Number 66/PP.06.4-Kpt/03/KPU/II/2020 on the Technical Guidelines for Formation of the PPK, PPS, PPDP (voter data updating personnel) and KPPS (voting groups) in the Elections. The requirements of the PPK and PPS Sekretariat is contained in the mentioned KPU Decree, and it is limiting, so that it does not provide opportunities for Civil Servants that do not come from the concerned District and Village/Sub-district. This situation becomes the cause of dual loyalty. The Civil Servant or Staff on the District/Village/Sub-District level have responsibility duty to their institution while on the other hand they are the Ad hoc body supporting system, both PPK and PPS must carry out administrative functions. This research is the case study in the Simultaneous Election in the Semarang Regency, and it uses the primary and secondary data of the Semarang Regency KPU. The research results conclude that PPK and PPS Sekretariat were more loyal with their main duty as the Civil Servant in the District/Village/Sub-district which resulted in the delay of the Finance Accountability Report preparation, late payment for the Ad hoc body, so the function as the supporting system for PPK and PPS could be realized. Indonesia’s National Government Internal Auditor of the Central Java Province linier review result stated that there was a delay of the submission of the Finance  Accountability Report from KPPS to PPS and PPK, which affected the submission to the Regency General Elections Commission which was due to the dual loyalty